EVOLUTION OFDEFINITIONS «innovation» in the theory ofeconomic schools - P. Gureev (Вестник университета)
Annоtation. The article describes the process of definition of «Innovation» as an object of scientific research in the schools of different directions. Are differences between the concepts imitation, invention and innovation. Formulated author's definition of the definition of «innovation»